2018
DOI: 10.1093/cid/ciy889
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pertussis Infections in the United States, 2011–2015

Abstract: Background The incidence of pertussis in the United States has increased in recent years. While characteristics of severe pertussis infection have been described in infants, fewer data are available in older children and adults. In this analysis, we characterize pertussis infections in hospitalized patients of all ages. Methods Cases of pertussis with cough onset from 1 January 2011 through 31 December 2015 from 7 US Emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 18 publications
4
85
0
1
Order By: Relevance
“…Of the three hospitalized patients who died, one was an infant aged 42 days and two were adults with underlying medical conditions: one 48-yearold adult who had a history of human immunodeficiency virus and one 76-year-old adult who had a previous history of asthma and COPD. 24 Asthma Three studies have shown that individuals with underlying asthma are at increased risk of pertussis diagnosis compared to individuals without, as further illustrated by two case studies ( Figure 3). [28][29][30][31][32] A retrospective, population-based case-control study compared the history of asthma in children and adults who had pertussis (confirmed by polymerase chain reaction, PCR) with age-and sex-matched controls during a pertussis outbreak between 2004 and 2005 in California, USA.…”
Section: Includedmentioning
confidence: 94%
See 1 more Smart Citation
“…Of the three hospitalized patients who died, one was an infant aged 42 days and two were adults with underlying medical conditions: one 48-yearold adult who had a history of human immunodeficiency virus and one 76-year-old adult who had a previous history of asthma and COPD. 24 Asthma Three studies have shown that individuals with underlying asthma are at increased risk of pertussis diagnosis compared to individuals without, as further illustrated by two case studies ( Figure 3). [28][29][30][31][32] A retrospective, population-based case-control study compared the history of asthma in children and adults who had pertussis (confirmed by polymerase chain reaction, PCR) with age-and sex-matched controls during a pertussis outbreak between 2004 and 2005 in California, USA.…”
Section: Includedmentioning
confidence: 94%
“…24 Asthma (and/or COPD) exacerbations were among the most frequent diagnoses leading to pertussisrelated hospitalizations in both adolescents and adults. 24 An increased all-cause and pertussis-related hospital admission rate was also observed for pertussis patients with asthma compared to controls at 45 days, 3 months, or 6-months postpertussis diagnosis. 30 In a case-control study in Finland in 1999, involving 103 adults with stable asthma (53 mild, 50 moderate) and 30 healthy controls, B. pertussis was detected by PCR in the sputum of 28.3% of mild asthmatics, in 20.0% of moderate asthmatics, and in 16.7% of controls.…”
Section: Includedmentioning
confidence: 99%
“…35 Lastly, the findings from a recent study led by authors from CDC, which evaluated severe pertussis infections across various states in the US during the period 2011-2015, showed that 14.5% of patients aged 21-64 years and 26.8% of those ≥65 years who were hospitalized for pertussis also presented with COPD indicating that underlying COPD may contribute to the clinical severity of pertussis infections. 36 Age-related changes in adaptive and humoral immunity in adults result in immunosenescence, i.e., a diminished immune response against certain diseases. 37 These changes can not only result in infections in such susceptible adults but also result in them becoming reservoirs of the causative agents, infecting those who cannot be vaccinated.…”
Section: Clinical Evidence On the Association Of Copd And Pertussismentioning
confidence: 99%
“…A total of 4477 children, who were included in our study, were diagnosed as having pertussis. The standard for clinical diagnosis of pertussis was not only based on the criteria (Mbayei et al, 2018), but also confirmed as follows: (1) Culture for B. pertussis or PCR for Bordetella-DNA from respiratory samples were positive;…”
Section: Patientsmentioning
confidence: 99%